96-1x=82

Simple and best practice solution for 96-1x=82 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 96-1x=82 equation:


Simplifying
96 + -1x = 82

Solving
96 + -1x = 82

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-96' to each side of the equation.
96 + -96 + -1x = 82 + -96

Combine like terms: 96 + -96 = 0
0 + -1x = 82 + -96
-1x = 82 + -96

Combine like terms: 82 + -96 = -14
-1x = -14

Divide each side by '-1'.
x = 14

Simplifying
x = 14

See similar equations:

| 4x^2+2x^3+18=0 | | 8.1-13.5=2.9 | | x/20x+1=10-3/1 | | 0.33333(6+9t)=5t-20 | | 4x^2-12x=36 | | -2w-10=10-4w | | -3+11=2 | | 5d+7=4d-9 | | 7(5a-4)-1=-8a | | -4(b-1)=-b-27 | | -8p+4=-4p-32 | | 12x-65=55 | | y-3=4x-(-2) | | t-8.1-13.5=2.9 | | 4(6m-6)=8m+40 | | 9x^2+18x+81=84 | | 67-(4x+8)=4(x+8)+x | | 2000/2= | | .09=0.4m | | 4(6m-6)=8m+49 | | 7-3v=-2v+2 | | .50x-4=2-.50 | | 3y^2-12y+12=0 | | -2(x-3)+4x=-(-x+11) | | x+82.7=63.4 | | (D^6-4d^4)y=0 | | -1.67+y=2.39 | | 1.2g+110.9=121.7 | | 42+3x=15 | | c-7=47 | | 1-2s=-3s+9 | | 0.3+1.2=3 |

Equations solver categories